2020
DOI: 10.5213/inj.2040076.038
|View full text |Cite
|
Sign up to set email alerts
|

Management of Urinary Incontinence With Underactive Bladder: A Review

Abstract: Urinary incontinence is caused by storage function failure, while underactive bladder (UAB) is caused by a decline in detrusor contractility and voiding dysfunction. As the treatment mechanisms for incontinence and UAB are contrary to each other, it is difficult to treat both incontinence and UAB, and the patient’s quality of life can be further degraded. Conventional midurethral sling (MUS), such as transobturator tape or retropubic MUS, introduces a risk of postoperative voiding dysfunction in stress urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…These findings suggest that contractile changes associated with bladder fibrosis constitute a complicated process that results in impaired bladder contractility with or without detrusor overactivity. Furthermore, the process of a coexistent voiding problem that is not associated with bladder fibrosis (e.g., stress urinary incontinence) can be a factor that induces incontinence [18][19][20]. Moreover, Uren et al [21] reported that patients diagnosed with DU using a urodynamic study showed nocturia, frequent daytime urination, urgency, and incontinence, as well as a weak urinary stream, hesitancy, and abdominal straining during urination.…”
Section: Luts and Decreased Contractility And Compliance Of The Bladder Detrusor Associated With Bladder Fibrosismentioning
confidence: 99%
“…These findings suggest that contractile changes associated with bladder fibrosis constitute a complicated process that results in impaired bladder contractility with or without detrusor overactivity. Furthermore, the process of a coexistent voiding problem that is not associated with bladder fibrosis (e.g., stress urinary incontinence) can be a factor that induces incontinence [18][19][20]. Moreover, Uren et al [21] reported that patients diagnosed with DU using a urodynamic study showed nocturia, frequent daytime urination, urgency, and incontinence, as well as a weak urinary stream, hesitancy, and abdominal straining during urination.…”
Section: Luts and Decreased Contractility And Compliance Of The Bladder Detrusor Associated With Bladder Fibrosismentioning
confidence: 99%
“…The re-adjustable sling can be a better option for the patients who have a recurrent SUI with detrusor underactivity to avoid postoperative voiding difficulty [72]. When the revision is A c c e p t e d A r t i c l e planned for postoperative voiding difficulty, it should be noted that complete excision of the mesh can produce a higher incidence of SUI recurrence compared with partial excision or urethrolysis [65].…”
Section: Postoperative Lower Urinary Tract Symptomsmentioning
confidence: 99%
“…In their article, "Management of Urinary Incontinence With Underactive Bladder: A Review" Cho and Kim [1] discuss different approaches to the management of urinary incontinence in patients with underactive bladder (UAB). As the authors point out, incontinence treatment requires that either the detrusor activity is decreased, which is the treatment principle in overactive bladder/detrusor overactivity, or that the bladder outlet resistance is increased, as is the basis for management of stress urinary incontinence (SUI) caused by e.g., intrinsic sphincter insufficiency or urethral hypermobility.…”
mentioning
confidence: 99%
“…Continence is dependent on the interaction between the urethral sphincter and the detrusor, and since the functional importance of each of these components may vary, the therapeutic problem in the individual patient is to find a suitable balance between them. In patients with both SUI and DU, Cho and Kim [1] point out the advantages and high success rate of conventional midurethral and adjustable slings. In most studies cited, there were no differences between SUI patients with or without DU.…”
mentioning
confidence: 99%
See 1 more Smart Citation